Neoadjuvant radiotherapy for rectal cancer: meta-analysis of randomized controlled trials - Rahbari, Nuh Nabi; Elbers, Heike; Askoxylakis, Vasileios; Motschall, Edith; Bork, Ulrich; Büchler, Markus W.; Weitz, Jürgen; Koch, Moritz (Annals of surgical oncology, 2013)
Although neoadjuvant radiotherapy may improve local control of rectal cancer, its clinical value requires further evaluation as a result of potential side effects and advances in surgical technique. A meta-analysis was performed to assess effectiveness and safety of neoadjuvant radiotherapy in the management of rectal cancer.
Gesehen am 13.12.2021